2007
DOI: 10.1620/tjem.212.71
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Quality of Life According to the Severity of Malocclusion in Japanese Orthodontic Patients

Abstract: Although quality of life (QOL) assessment is important in dentistry, it has not been fully investigated in orthodontic patients. We investigated the health-related generic QOL (entire body health) and disease specific QOL (oral health) in adult patients with malocclusions at the first visit. One hundred and twenty-seven orthodontic patients and 66 persons with normal occlusion were recruited for the study. The subjects were divided into the three following groups based on their treatment: 61 patients in need o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
2
25
2
6
Order By: Relevance
“…10,12,[20][21][22][23] The mean total score of 53.5 in this cohort is three points above the previously reported 21 highest score in the literature. Proportionally, the domains in this study that were of most concern to individuals were social impact and esthetics, both 15% higher than mean scores from other authors' studies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…10,12,[20][21][22][23] The mean total score of 53.5 in this cohort is three points above the previously reported 21 highest score in the literature. Proportionally, the domains in this study that were of most concern to individuals were social impact and esthetics, both 15% higher than mean scores from other authors' studies.…”
Section: Discussionmentioning
confidence: 64%
“…18 Motivation for patients to seek treatment can be broadly split into three main areas: an exclusively practical problem, an exclusively psychological problem, or, most likely, a combination of both. 3 It has been proposed 20 that patients with increased social QoL concerns are more likely to seek surgical intervention than are those with a purely esthetic concern. Our results show that females are both more aware of their appearance and more likely to complain of an increased social impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the patients' morphological deformities, we set up a Severity Score (SS) for each patient based on their cephalometric radiographs which were traced and lined, and the angular and plaster model measurements were assessed. The Severity Scores were used to assess the patients' dentofacial deformities, and defi ned in Table 1 (Tajima et al 2007).…”
Section: Subjectsmentioning
confidence: 99%
“…We have recently reported that the patients with malocclusions especially in need of surgical correction had lower disease-specifi c HRQOL (Tajima et al 2007). However, even after orthodontic treatment by the expert dentists, patients show large variations in the level of satisfaction (Kiyak et al 1982;Flanary et al 1990;Enomoto et al 2000;Cunningham et al 2002).…”
Section: Subjectsmentioning
confidence: 99%